PERAN ORANG TUA DALAM MENDIDIK MORAL ANAK USIA 12-17TAHUN DI DESA BOTI-KECAMATAN KIE-KABUPATEN TIMOR TENGAH SELATAN - Cindy Kore Mega; Hendrik A.E. Lao, Andrian Wira Syahputra (CV. ADIBA AISHA AMIRA, 2024)
This research aims to investigate the moral development of adolescents aged 12- 17, particularly in the village of Boti, Kie District, South Central Timor Regency, along with the methods employed by parents in shaping their moral compass. Employing a qualitative descriptive approach, the study collected data through interviews, observations, and documentation. The findings encompass several aspects: Firstly, there exists a spectrum of moral behavior among the adolescents, ranging from those who are respectful and courteous towards elders to those who exhibit less desirable conduct towards peers and others. Secondly, parents utilize methods such as advising, demonstrating good habits, and serving as role models to instill moral values in their children. Thirdly, impediments to moral education include negative peer influence in the local environment, parental neglect, and the impact of technology. However, strong familial and positive environmental support serve as significant facilitating factors.